Should Parents of the Deceased Have Standing to Initiate Posthumous Sperm Retrieval? Analyzing Developments in Israel - Amir, Roee (The Hastings Center report, 2026)
Posthumous sperm retrieval is a complex and contentious issue that raises various ethical, legal, and social concerns. Policies regulating this practice vary globally, reflecting diverse normative approaches and cultural values. Israel, which had a permissive stance on the matter even before the October 7 attack, has seen a significant shift in policy since the attack and subsequent war, now allowing sperm retrieval based on parental request. This development, partly driven by a desire to honor fallen soldiers, adds new complexity to the ethical discourse. This paper uses Israel's policy shift as a starting point to explore whether parents of the deceased should be granted a right to initiate the procedure, particularly in the context of war and national loss. The discussion navigates a web of competing interests and narratives that require careful untangling, including the deceased's autonomy and bodily integrity, the relatives’ desire for genetic continuity, the potential for conflict between relatives with opposing wishes, the welfare of potential offspring, and broader societal implications with special attention to the tension between honoring sacrifice and respecting individual reproductive choices.